Perspectives of Children and Youth With Disabilities and Special Needs Regarding Their Experiences in Inclusive Education: A Meta-Aggregative Review - Paul, Tithi; Di Rezze, Briano; Rosenbaum, Peter; Cahill, Peter; Jiang, Annie; Kim, Eileen; Campbell, Wenonah (Frontiers in Education, 2022)
Inclusive education is important to achieve high-quality education for all; however, there is an important gap in the literature surrounding inclusive education, namely representation of the perspectives of children and youth with disabilities and special needs. In this study, we used a meta-aggregative approach to qualitative evidence synthesis to bring together systematically the perspectives of these children and youth regarding their experiences in inclusive education, and to generate recommendations for action. After selecting and critically appraising the methodological quality of eligible qualitative studies, we extracted the findings from the results sections of 27 studies involving children and youth with various diagnoses and special needs. We aggregated the findings to develop 19 categories, which we further synthesized into six overarching statements pertaining to: (i) teachers’ and education workers’ support and attitudes; (ii) implementation of support and accommodations; (iii) need for safe and accommodating physical environment; (iv) preparation for high school transitions; (v) friendships and peer interactions; and (vi) participants’ own views of themselves. Implications of our findings include: (i) a need for strong leadership at the school level to support implementation of inclusive education; (ii) a need for leadership from government agencies and schools to provide opportunities for teachers to train and collaborate with other professionals; and (iii) a need for flexibility in curriculum and instruction, for which educators require training and experience. Most importantly, our findings show that children and youth with disabilities and special needs, when provided opportunities, demonstrate profound personal understandings of their strengths and needs, their conditions and how these impact their lives, leading to insightful information that can enhance inclusive education practice and policy.